Paths of ethnohistory in Peru - Deustua, José (1980)
Pablo Macera in his History in Peru: science and ideology mentioned the dissolution of historical work within the concerns of anthropology and sociology, back in the 1950s. As such, ethnohistory in Peru, which consists of the maintenance of ethnological concerns within historical research, is a young science, where María Rostworoski de Diez Canseco will constitute one of its most serious representatives.